Spread Sea Clutter Suppression in HF Hybrid Sky-Surface Wave Radars Based on General Parameterized Time-Frequency Analysis - Zhuo-qun Wang; Ya-jun Li; Jun-nan Shi; Peng-fei Wang; Ai-hua Liu; Xin-fan Xia; De-hong Chen (International Journal of Antennas and Propagation)
In high-frequency (HF) hybrid sky-surface wave radar, the first-order sea clutter broadening is severe under the action of ionospheric phase disturbance and bistatic angles. In this paper, a cascaded method is described to suppress the spread sea clutter. Firstly, the radar configuration and sea clutter broadening model are introduced based on the newly developed integrated HF sky-surface wave experimental system. In the cascaded processing method, a new ionospheric decontamination method based on general parameterized time-frequency (GPTF) analysis is proposed to estimate or correct the ionospheric phase distortion with large amplitude. Then, the forward-backward linear prediction (FBLP) algorithm is used to suppress the spread sea clutter caused by bistatic angle. Simulation results show that such ionospheric decontamination method based on GPTF is helpful for the large-amplitude ionospheric contamination when the target masking effect happens even after ionospheric phase decontamination. Finally, the proposed method is examined by the measured data. Experimental results indicate that the proposed method can well suppress the broadening sea clutter for HF hybrid sky-surface wave radars.